ESOP VS SWEAT EQUITY– A COMPARISON OF BENEFICAL IMPACT TO EMPLOYEES-A STUDY WITH SPECIAL REFERENCE TO CHENNAI, HYDERABAD & RAJASTHAN - K.S. Meenakshisundaram,; S T Krishnekumaar,; K N Usha, (International Journal of Psychosocial Rehabilitation, 2020)
Employees Stock Ownership Plan (ESOP) are given in the nature of Incentive and retention plan and these are issued to employees and officers. These options are issued with conversion right at a pre-determined price and the issue price can be less than the intrinsic value of the shares. SWEAT EQUITY Shares (SE) are issued as consideration for creation or transfer of IPRs to the company or as other value addition these are issued to the employees, Officers and Directors of the Company. These shares are issued at discounted price or even free for know-how and services to the company. ESOP is granted to employees normally in the Senior Management level even though such contributions arise from grass root level and there is no review mechanism for this grant either by the Internal and External auditors or by the Regulator viz., SEBI which is again like performance appraisal resulting in favoritisms and demotivation among the employees. In order to understand the perquisite which is beneficial for the employees between ESOP and SE, this study was conducted in the Cities of Chennai, Hyderabad & Rajasthan in India and primary data were collected from 374 employees working in Manufacturing, Banking, IT & ITES, Construction / Real Estate and FMCG sectors. . Both Primary and secondary data were collected. It was found that 301 respondents were found to be allotted with ESOP and SE and in between the two majority of them were found to be with ESOP and the balance of 73 respondents were not allotted any shares. The results reveal that for the purpose of Job security, the Junior level and Middle level management has agreed that, there exists a review mechanism both Internal and Regulatory but whereas the Senior Management is always sail with the Tactical Management and Board in order not to lose any benefit.